2012
DOI: 10.1002/anie.201207335
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of an Early Postulate: BCB Two‐Electron–Three‐Center Bonding in Organo(hydro)boranes

Abstract: Finally, boron did it too: The first example of a dimeric organyl(hydro)borane with a B-B-bridging aryl ring has been elucidated (see picture; B green/blue, C black/gray). It features a B-C-B two-electron-three-center bond and a largely unperturbed aromatic π-electron system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 42 publications
2
91
0
2
Order By: Relevance
“…[43] Thec ompound, obtained from the reduction of the aryldihydroborane dimer [(MPind)BH 2 ] 2 with lithium, followed by two consecutive LiH abstraction steps,was isolated as the staggered D 2d isomer and is the first diborane(4) to display terminal hydrogen atoms (Scheme 7). [45] While reduction with al arge excess of Li in thf yielded the dianionic 8b,16b-(diborata)dibenzo-[g,p]chrysene (23), which has af ormal B = Bd ouble bond [1.641(6), 1.627(6) ], reduction with 2o r4molar equivalents of lithium naphthalenide in thf yielded two isomeric diborane(6) dianions with BÀBs ingle bonds,c ompounds 24 and 25,r espectively [BÀB: 24 1.810(5), 25 1.789 (7) ]. [44] More recently,W agner and co-workers demonstrated the variety of B À Bb onds that may be obtained by reduction of the hydride-bridged bis(2,2'-biphenyl)diborane 22,acompound ideally preorganized for reductive BÀBc oupling (Scheme 8).…”
Section: Selective Reductive Coupling Of Arylboranesmentioning
confidence: 99%
“…[43] Thec ompound, obtained from the reduction of the aryldihydroborane dimer [(MPind)BH 2 ] 2 with lithium, followed by two consecutive LiH abstraction steps,was isolated as the staggered D 2d isomer and is the first diborane(4) to display terminal hydrogen atoms (Scheme 7). [45] While reduction with al arge excess of Li in thf yielded the dianionic 8b,16b-(diborata)dibenzo-[g,p]chrysene (23), which has af ormal B = Bd ouble bond [1.641(6), 1.627(6) ], reduction with 2o r4molar equivalents of lithium naphthalenide in thf yielded two isomeric diborane(6) dianions with BÀBs ingle bonds,c ompounds 24 and 25,r espectively [BÀB: 24 1.810(5), 25 1.789 (7) ]. [44] More recently,W agner and co-workers demonstrated the variety of B À Bb onds that may be obtained by reduction of the hydride-bridged bis(2,2'-biphenyl)diborane 22,acompound ideally preorganized for reductive BÀBc oupling (Scheme 8).…”
Section: Selective Reductive Coupling Of Arylboranesmentioning
confidence: 99%
“…Other computational work [70] has suggested that phosphinoboranes should dehydrogenate alcohols to ketones and aldehydes. The antiaromatic nature of dibenzoborole [71][72][73][74] led to the prediction of high reactivity for the phosphinoborane 25 and indeed it reacts rapidly with 1 atm H 2 to give phosphine-borane 43 (Scheme 17) [26].…”
Section: Lewis Acid/base Propertiesmentioning
confidence: 99%
“…[12,13] However, convenient access to silafluorenes with an asymmetric substitution pattern in the 4-positions is lacking as of yet. A number of synthetic routes towards 9-silafluorenes have been reported earlier (cf.…”
Section: Introductionmentioning
confidence: 99%